Porous membranes integrated into electrochemical systems for bioanalysis - Kosuke Ino; Yoshinobu Utagawa; Kaoru Hiramoto; Hiroya Abe; Hitoshi Shiku (Electrochemical Science Advances)
Abstract Porous membranes have emerged as promising platforms for bioanalysis because of their unique properties including high surface area, selective permeability, and compatibility with electrochemical techniques. This minireview presents an overview of the development and applications of porous membrane‐based electrochemical systems for bioanalysis. First, we discuss the existing fabrication methods for porous membranes. Next, we summarize electrochemical detection strategies for bioanalysis using porous membranes. Electrochemical biosensors and cell chips fabricated from porous membranes are discussed as well. Furthermore, porous micro‐/nanoneedle devices for bioapplications are described. Finally, the utilization of scanning electrochemical microscopy for cell analysis on porous membranes and electrochemiluminescence sensors is demonstrated. Future perspectives of the described membrane detection strategies and devices are outlined in each section. This work can help enhance the performance of porous membrane‐based electrochemical systems and expand the range of their potential applications.